Research and Simulation of Metro Pantograph-catenary SystemBased on Least Square Support Vector Machine - Jiang Wei; Huang Yuping (机车电传动)
A model of pantograph-catenary system based on the error correlation was put forward, and the least squares supportvector machine (LSSVM) method was used to study the parameters of the model. The error correlation coefficient was analyzed, andbased on existing lines actual test data, pantograph-catenary contact pressure value was simulated and analyzed. The results showed thatthe pantograph-catenary model based on least squares support vector machine could describe the dynamic behavior of contact pressurewith high forecast precision.